Tinjauan Atas Inovasi Produk Pada Cafe Dua Tiga Coworking Bogor - Fadillah, Adil; Elsiana, Elsiana (Jurnal Ilmiah Pariwisata Kesatuan, 2022)
Currently, business competition is increasingly fierce, requiring us to always think creatively in building a business. This situation results in the level of competition in gaining and retaining consumers being very high. The business of opening a coffee shop turns out to be profitable for many parties, so it has an influence on Indonesia's creative economy. These parties include: business entrepreneurs, consumers, and workers. Business entrepreneurs get big opportunities and income. In the business world, innovation and creativity are things that need to be done for the development and success of a business. Every company must create innovations to expand into new markets and maintain their current market share. One innovation that can be developed is through product innovation.The objectives of this research are: To find out the product innovations that have been carried out by Cafe Two Three Coworking Bogor, to find out the superiority of product innovation at Cafe Two Three Coworking Bogor, to find out consumer evaluations of product innovation at Cafe Two Three Coworking Bogor.The results of this research show that the product innovations carried out at the Two Three Coworking Cafe in Bogor include food products and beverage products. In pizza products, two or three coworking cafés in Bogor have innovated by making pizza volcanoes. Meanwhile, the beverage products that have been innovated by cafe two three coworking Bogor are Baileys Coffee, Es Kopi Susu Pandan and Es Kopi Susu Moccacino. Meanwhile, the superiority of the food product, the superiority of the pizza food product, is of course in terms of the wider serving size and the taste of the volcano pizza which shows more of the taste of cafe two three coworking Bogor style pizza, and apart from that the superiority of the coffee drink product at the two three coworking cafe Bogor, every purchasing coffee will get a loyalty card. Meanwhile, the evaluation carried out by cafe two three coworking Bogor carried out the latest innovations in every beverage and food product.The conclusion of this research is, the innovation carried out by cafe two three coworking Bogor on pizza products, pizza meat lover food products before innovation and after innovation became pizza volcano. Meanwhile, the beverage products are iced milk coffee which has not yet been innovated by cafe two three, and which after being innovated has become bailyes coffee, pandan milk iced coffee and moccacino milk iced coffee. Meanwhile, the advantage of the beverage product is the superiority of the coffee drink product at Cafe Two Three Coworking Bogor, every time you purchase coffee you will get a loyalty card. And the advantages of the pizza volcano food product are: For the advantages of the pizza food product, of course, in terms of the wider serving size and the taste of the volcano pizza, it shows more of the taste of two three coworking cafe style pizza in Bogor because the taste is prepared directly from the chef. Meanwhile, the evaluation carried out by Cafe Two Three Coworking in Bogor involves making innovations in each food and beverage product in order to increase sales and win the coffee shop competition in the city of Bogor.